Interdisciplinary Approach for the Medical Management of Gestational Gigantomastia - Camila Cabrera; Mackenzy Radolec; Angela Prescott; Carolyn De La Cruz; Stacy Beck (Thieme Medical Publishers, Inc., 2020)
Background Gestational gigantomastia is a rare and debilitating condition that is thought to result from hormone hypersensitivity. Several definitions have been proposed using breast weight and change in body mass index, but the breast growth is best summarized as rapid, diffuse, and excessive. Case We report a case of a 31-year-old woman with a history of infertility and cystic fibrosis that developed pathologic breast growth during hormonal preparation for in vitro fertilization. Her serum laboratories were unremarkable, and she was medically managed until 31 weeks of gestation. After delivery, she experienced rapid decrease in breast size and was followed by plastic surgery with plan to allow spontaneous regression with interval breast reduction Conclusion We highlight a successful interdisciplinary medical management approach, which helped to avoid a morbid, intrapartum breast reduction.